The association of prenatal and childhood pyrethroid pesticide exposure with school-age ADHD traits. (March 2022) - Lee, Kyung-Shin; Lim, Youn-Hee; Lee, Young Ah; Shin, Choong Ho; Kim, Bung-Nyun; Hong, Yun-Chul; Kim, Johanna Inhyang
Graphical abstract: Highlights: Reports on the neurotoxic effect of pyrethroid insecticides have been inconsistent. Prenatal and age 2 3-phenoxybenzoic acid (3-PBA) levels were linked to ADHD symptoms at age 6. 3-PBA levels at age 4 and 6 lead to ADHD symptoms at age 8. The effect of 3-PBA on ADHD symptoms differed according to exposure period. Abstract: Background: Pyrethroid insecticides are commonly used in residential settings, and their use has increased rapidly. Although research has been scarce, they have been reported to be associated with impaired neurodevelopment. Moreover, susceptible exposure windows and the long-term effects of pyrethroids have not been investigated. We examined the association between pyrethroid exposure and attention-deficit/hyperactivity disorder (ADHD) symptoms over time, with exposure windows spanning from the prenatal period to school-age. Methods: Using 524 mother–child pairs, we measured urinary concentrations of 3-phenoxybenzoic acid (3-PBA), a major pyrethroid metabolite, and asked parents to fill-out the ADHD Rating Scale IV (ARS). We used Poisson regression to identify the susceptible periods of pyrethroid exposure, by correlating various 3-PBA exposure windows (prenatal, ages 2, 4, 6 and 8) with ADHD symptoms at ages 6 and 8. Results: Doubling of prenatal and age 2 3-PBA concentrations was associated with increased ADHD symptoms at age 6 (2.7% change, 95% confidence interval [CI]: 0.3, 5.2; 5.2% change [95% CI: 0.5, 10.2], respectively). The 3-PBA concentrations at age 4 and age 6 were linked with ADHD symptoms at age 8 (2.7% change [95% CI: 0.3, 5.3]; 3.3% change [95% CI: 0.2, 6.4], respectively). There were no clear sex-specific patterns in association. Discussion: Both prenatal and early-childhood exposure to 3-PBA were found to be associated with ADHD symptoms. Exposure during pregnancy, and at ages 2 to 6 were found to be susceptible periods for pyrethroid neurotoxicity at ages 6 and 8.